ELEMENTS OF URBAN DESIGN IN MODERN CITY ARCHITECTURAL PARTERRE FORMATION - Dubinskiy V. P.; Skorobohatko O. V. (World Science, 2019)
The article deals with the problem of architectural parterre as an environmental object in urban realm structure. Tendencies in urban building are described, resulting in architectural parterre formation. The rates of urban density and number of floors, where architectural parterre is formed, are provided. The description of 3-D elements, that are included in architectural parterre structure, is indicated. This article gives the analysis of architectural parterre human perception peculiarities. On the grounds of conducted analysis, the article presents urban design elements, by means of which the architectural-artistic appearance of architectural parterre is formed. The article makes a description of the urban design revealed elements and systematizes them.